2022
DOI: 10.1108/gm-02-2022-0040
|View full text |Cite
|
Sign up to set email alerts
|

Global perspectives on gender diversity and business performance

Abstract: Purpose Based on the resource-based theory, the purpose of this study is to investigate the relationship between operational employment levels of gender diversity and business performance over a multi-year period. This study also explores if gender parity moderates this relationship and how gender diversity is directionally developed. Design/methodology/approach A cross-lagged panel design and path analysis is applied to a global data set of women employees, women managers and women senior executives – in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…These results are consistent with those of various studies indicating the active role played by EBPs in the field of special education and its positive impact on both the teacher and the student (Al-Gahtani & Al-Johani, 2022;Al-Malky & Alrasheed, 2023;Al-Omari & Al-Zaraa, 2022;Al-Otaibi, 2022;Al-Shammari et al, 2021; http://ijlter.org/index.php/ijlter Andronache et al, 2014;Casale-Giannola et al, 2023;Fouad, 2022;Layden et al, 2022). These results also agree with Maghraby's study (2022) in that the attitudes of IETs toward their students with ID were positive.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with those of various studies indicating the active role played by EBPs in the field of special education and its positive impact on both the teacher and the student (Al-Gahtani & Al-Johani, 2022;Al-Malky & Alrasheed, 2023;Al-Omari & Al-Zaraa, 2022;Al-Otaibi, 2022;Al-Shammari et al, 2021; http://ijlter.org/index.php/ijlter Andronache et al, 2014;Casale-Giannola et al, 2023;Fouad, 2022;Layden et al, 2022). These results also agree with Maghraby's study (2022) in that the attitudes of IETs toward their students with ID were positive.…”
Section: Discussionsupporting
confidence: 90%
“…Hypothesis 1 is therefore not supported, which means we cannot conclude that female CEOs perform beter than male ones. We hypothesized a posi�ve rela�onship between female CEOs and financial performance based on several studies (e.g., Nekhilli et al, 2018;Chadwick and Dawson, 2018;Fouad et al, 2023;Fernando et al, 2023). However, our results acknowledge the mixed findings in exis�ng literature regarding this rela�onship.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Various explana�ons are given as to why female CEOs achieve a beter financial return, such as women think more market-oriented (Davis et al, 2010), understand the market beter (Strom et al, 2014), are beter advisors (Adams and Ferreira, 2007), can beter maintain rela�onships leading to a beter business environment (Shrader et al, 1997), take fewer personal benefits than men (Barber and Odean, 2001;Bliss and Poter, 2002), and manage the expenditure of financial resources beter (Barber and Odean, 2001;Bliss and Poter, 2002;Khan and Vieito, 2013). The results of Fouad et al (2023) recently confirmed a posi�ve rela�onship between women managers and revenue over a mul�-year period for all companies. Similarly, Fernando et al (2023) show that increasing female representa�on in the top management team has a substan�al and direct posi�ve influence on firm performance.…”
Section: The Link Between Gender and Financial Performancementioning
confidence: 99%